The Influence of Altered-Gravity on Bimanual Coordination: Retention and Transfer - Diaz-Artiles, Ana; Wang, Yiyu; Davis, Madison M.; Abbott, Renee; Keller, Nathan; Kennedy, Deanna M. (Frontiers in Physiology, 2022)
Many of the activities associated with spaceflight require individuals to coordinate actions between the limbs (e.g., controlling a rover, landing a spacecraft). However, research investigating the influence of gravity on bimanual coordination has been limited. The current experiment was designed to determine an individual’s ability to adapt to altered-gravity when performing a complex bimanual force coordination task, and to identify constraints that influence coordination dynamics in altered-gravity. A tilt table was used to simulate gravity on Earth (90° head-up tilt (HUT)) and microgravity (6° head-down tilt (HDT)). Right limb dominant participants (N=12) were required to produce 1:1 in-phase and 1:2 multi-frequency force patterns. Lissajous information was provided to guide performance. Participants performed 14, 20 s trials at 90° HUT (Earth). Following a 30-minute rest period, participants performed two retention trials (Earth) followed by two transfer trials in simulated microgravity (6° HDT) for each coordination pattern. Results indicated that participants were able to transfer their training performance during the Earth condition to the microgravity condition with no additional training. No differences between gravity conditions for measures associated with timing (interpeak interval ratio, phase angle slope ratio) were observed. Despite the effective timing of the force pulses, however, there were differences in measures associated with force production (peak force, mean force, STD of force). The results of this study suggest that Lissajous displays may help counteract manual control decrements observed during microgravity. Future work should continue to explore constraints that can facilitate or interfere with bimanual control performance in altered-gravity environments.